Analisis Model-model Pembelajaran - Putri Khoerunnisa; Syifa Masyhuril Aqwal (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
This study aims to how to understand teaching models. And to find out what are the main models of teaching. Teaching models in a sense are seen as more prominent and relevant to the guidance of the world education needs of the world today. Modification, especially to some teaching methods, compilation do it fully in the framework of developing or adjusting to the needs. As prospective teachers and professional teachers are also expected to make adjustments as necessary to the model if it is necessary to match the teaching-learning context which may be different from what is compiling in this section. Learning design is practice the formulation of communication and media technology media to help effectively transfer knowledge between teachers and students. Learning design is also a design of the learning process based on the needs and learning objectives and delivery system so that it becomes a reference in its implementation to create effective and efficient learning by minimizing the difficulty of students in understanding learning. On the personal development of students by paying more attention to the realm of sense, especially in emotional. the help of the personal model family is more emphasized on the formation and organization of the reality of environmental life and unique life. Hopefully, using this learning model the process of teaching and learning can help students develop their own productive relationships with their environment. Students as students can also realize themselves himself as a